2021
DOI: 10.4103/wjnm.wjnm_39_20
|View full text |Cite
|
Sign up to set email alerts
|

Oligometastasis to testis in prostate cancer: Role of gallium-68 prostate-specific membrane antigen positron-emission tomography computed tomography

Abstract: Accurate staging and restaging with early detection of recurrent site is the key for planning treatment in patients of prostate cancer. Recently, gallium-68 prostate-specific membrane antigen positron-emission tomography computed tomography ( 68 Ga-PSMA PET/CT) has emerged as a better tool for this. Few uncommon sites of early metastasis can also be identified in addition to the other common sites. Herein, we present three cases of early metastasis to testis in prostate cancer identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…An autopsy study reported a prevalence of testicular metastases among men with PCa equal to 0.5%, while another study of histological analysis of the testicular tissue from patients, who underwent androgen deprivation orchidectomy for advanced PCa, resulted in a prevalence of 0.18% and presence of disease with atypical biologic behaviour and poor prognosis 13,14 . In the more recent series, testicular metastases are discovered through modern imaging methods, mainly PSMA PET/CT, in the context of detecting the focus underneath biochemical recurrence, and confirmed through histological analysis 15 . A PSMA PET/CT‐detected testicular metastasis can be the solitary focus of disease recurrence, which may be diagnosed more than 10 years after the definitive PCa treatment 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An autopsy study reported a prevalence of testicular metastases among men with PCa equal to 0.5%, while another study of histological analysis of the testicular tissue from patients, who underwent androgen deprivation orchidectomy for advanced PCa, resulted in a prevalence of 0.18% and presence of disease with atypical biologic behaviour and poor prognosis 13,14 . In the more recent series, testicular metastases are discovered through modern imaging methods, mainly PSMA PET/CT, in the context of detecting the focus underneath biochemical recurrence, and confirmed through histological analysis 15 . A PSMA PET/CT‐detected testicular metastasis can be the solitary focus of disease recurrence, which may be diagnosed more than 10 years after the definitive PCa treatment 16 …”
Section: Discussionmentioning
confidence: 99%
“…13,14 In the more recent series, testicular metastases are discovered through modern imaging methods, mainly PSMA PET/CT, in the context of detecting the focus underneath biochemical recurrence, and confirmed through histological analysis. 15 A PSMA PET/CT-detected testicular metastasis can be the solitary focus of disease recurrence, which may be diagnosed more than 10 years after the definitive PCa treatment. 16 T A B L E 3 Association of distal VDI positivity with nodal and surgical margin status in patients with pT3b pathology.…”
Section: Characteristicsmentioning
confidence: 99%
“…Thus, more and more teams, such as Manoj Gupta et al, diagnose testicular metastasis of prostatic carcinomas on PSMA PET/CT. 5 …”
Section: Discussionmentioning
confidence: 99%
“…9 Since it is a new technique, the number of cases in which testicular metastasis is detected with 68 Ga-PSMA in prostate cancer is limited. [10][11][12][13][14][15][16] Literature review via PubMed, MEDLINE and Embase database was carried out, and nine published cases published in English were identified between 2017 and August 2021 (Table 1). Of these reports, eight were treated with primary radical prostatectomy, and one with radiotherapy and hormone therapy.…”
Section: Discussionmentioning
confidence: 99%